An approximation of loop free energy values of RNA H-pseudoknots. - Gultyaev, A P (1999)
A set of free energy values is suggested for RNA H-pseudoknot loops. The parameters are adjusted to be consistent with the theory of polymer thermodynamics and known data on pseudoknots. The values can be used for estimates of pseudoknot stabilities and computer predictions of RNA structures.